PENGARUH EDUKASI GIZI TERHADAP PENGETAHUAN GIZI, SIKAP, DAN POLA MAKAN PADA PASIEN DIABETES TIPE 2 DI PUSKESMAS KECAMATAN CIRACAS - Nindy Apriliani Putri; Pritasari Pritasari (UHAMKA PRESS, 2017)
A good diet is a key factor in the handling of patient with Diabetes Mellitus (DM).Selection of the right foods can help controlling blood sugar. Consumption of foods with highfiber and low glycemic index can help controlling blood glucose levels in diabetic patients.Education is a way to improve the life quality of patients with DM. In this study, the methodused was the pre-experimental design with one group pre-test post-test and given nutritioneducation to patients with nutritional counseling using booklet media “High Fiber Diet andLow Glycemic Index” was expected can change the nutritional knowledge, attitude, and dietin patients with DM. Sampling method with purposive sampling with the total number ofsubjects were 66. Data analysis techniques with statistical test paired T-test. Based on thisresearch, it was known that there were significant differences in nutritional knowledge,attitudes, and a diet based on amount of the fiber intake and glycemic index food mix (p<0.01) between pre and post intervention of nutrition education.